2016
DOI: 10.1075/lab.14027.hop
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linguistic lexical and syntactic co-activation in L2 sentence processing

Abstract: This study investigates under which conditions the L1 syntax is activated in L2 on-line sentence comprehension. We study whether cross-linguistic syntactic activation of the L1 word order is affected by lexical activation of the first language (L1) by virtue of cognate words. In two eye-tracking experiments, German-English bilinguals and English natives read English sentences containing reduced relative clauses whose surface word order partially overlaps with German embedded clauses. The verbs used were either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
55
4
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 79 publications
12
55
4
7
Order By: Relevance
“…The purpose of these two experiments was to address whether cross-language activation during bilingual reading is sensitive to differences in language experience among bilinguals (such as the current exposure to the L2) and, crucially, to shifting language demands (such as a momentary shift in the language of the sentence). In line with the BIA+ model of word recognition (Dijkstra & Van Heuven, 2002) and many previous empirical studies (e.g., Gullifer et al, 2013;Hopp, 2016;Lauro & Schwartz, 2017; Pivneva et al, 2014;Titone et al, 2011;Van Hell & Dijkstra, 2002), we observed cross-language activation when French-English bilinguals read words within the context of sentences in their L2. Also in line with BIA+, evidence for cross-language activation was qualitatively much weaker when English-French bilinguals read in their L1.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The purpose of these two experiments was to address whether cross-language activation during bilingual reading is sensitive to differences in language experience among bilinguals (such as the current exposure to the L2) and, crucially, to shifting language demands (such as a momentary shift in the language of the sentence). In line with the BIA+ model of word recognition (Dijkstra & Van Heuven, 2002) and many previous empirical studies (e.g., Gullifer et al, 2013;Hopp, 2016;Lauro & Schwartz, 2017; Pivneva et al, 2014;Titone et al, 2011;Van Hell & Dijkstra, 2002), we observed cross-language activation when French-English bilinguals read words within the context of sentences in their L2. Also in line with BIA+, evidence for cross-language activation was qualitatively much weaker when English-French bilinguals read in their L1.…”
Section: Discussionsupporting
confidence: 90%
“…Also in line with BIA+, evidence for cross-language activation was qualitatively much weaker when English-French bilinguals read in their L1. Crucially, in contrast with BIA+ but in line with general models of bilingual language control (Abutalebi & Green, 2007;2016;Green & Abutalebi, 2013), cross-language activation of the L2 was significant during L1 reading, but only following a prior switch into the L2. This suggests that the control demands placed on the system by a switch into the second language may have required bilinguals to suppress the semantics of the L1, allowing for greater cross-language activation of the L2 downstream from a switch.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations